Vivência de transexuais e suas potencialidades humanas - Simão, Guilherme Faquim (2017)
Currently, Transsexuality is one of the various forms of sexual expression. It is understood as a disagreement between biological sex and gender by which the person is identified and would be socially recognized. Objective: To assess life attributes of transsexual people from a Specialized Service - TT outpatient clinic in a city in the interior of São Paulo state, and to understand the meanings and senses attributed by them to their trans-experience. Method: The study was carried out in two moments: first, quantitative, to assess and identify potentialities from Positive Psychology, for the prevention of possible mental disorders. For this, the following instruments were applied: Life Satisfaction Scale (LSS), Positive Affects (PA) and Negative (N A), Rosenberg Self-Steem, General Self-Efficacy, Test to Evaluate Optimism (LOT-R), Cognitive Hope and Dispositional Hope Scale. The second, qualitative on the phenomenological approach, whose interviews were carried out and mediated by the following question: "How is transsexual living for yourself?”. The instruments were quantitatively analyzed, and for the analysis of the reports, reading and re-reading, discrimination of units of meanings, elaboration of category and identification of convergences and divergences in discourses were used. Results: Based on a descriptive design, eight transsexuals, four male (MtF) and four female (FtM), mean age of 23 years (± 8.73) participated. The results of the scales indicated that most of the transsexuals presented results in average or over the average in their psychological attributes, when compared to the subjects evaluated for normalization of the instruments. In the analysis of the reports, the following categories were stood out: childhood experiences: self-perception; school experiences: bullying; experiences of adolescence: new discoveries; body experiences: hormonalization; family experiences: acceptance and discrimination; sexual affective relationships; social name. In the understanding / interpretation of the reports, childhood was distinguished by the doubt and inclination to the opposite gender since they were very small, and that the school environment could be threatening, excluding and permeated by the prejudice, which mainly contributes to the evasion. The adolescence transition goes through the experience of homosexuality until the recognition of their real gender identity, experienced by most transsexuals. Along with the recognition of their identity, the desire to be bodily readmitted through hormones and / or surgery is enhanced. Into the family environment, some people accept or not the transsexual condition, and the physical / verbal violence that many of them suffer when assuming their gender identity. Finally, the use of the social name was highlighted as a way of being recognized and legitimized as people and respected based on their gender identity. Further studies are necessary to carry out on this subject, especially in relation to the re-signification of the pathological and reductionist concept of transsexuality. Conclusion: Although they have experienced many adversities due to their transsexual condition, the collaborators presented several virtuous and healthy factors, showing, in general, as being hopeful, persevering and optimistic, presenting also similar experiences pointed out in most of their reports.